Modern Technologies in Foreign Language Teaching - Янбастиева-Петрова, Лина (Научни трудове, 2023)
Today’s education aims at preparing students for life and work in the 21st century, which requires gaining a number of skills and competences, including computer literacy and competence in foreign languages. Using ICTs may greatly improve the quality of the learning process. This article examines their role in foreign language instruction in the context of teaching representatives of generations Z and Alpha. It also discusses some current trends in educational politics in Bulgaria, and presents several online educational platforms and tools which have been used in ESL classes at Yoan Ekzarh Balgarski Secondary School, Shumen.
Keywords: Образование; Tехнология; Преподаване на чужди езици